2018
DOI: 10.3390/w10050580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Conditions and Morphometric Parameters on Surface Water Temperature in Polish Lakes

Abstract: The study evaluated the effect of environmental conditions and morphometric parameters on lake water temperature changes. The analysis was carried out on the basis of 14 lakes located in northern Poland. The assessment was based on the daily water and air temperatures from 1972 to 2016. It took into account the location of lakes (latitude, longitude, altitude) morphometric parameters (surface area, maximum and mean depth, volume), hydrological processes (rate of water exchange, course of ice phenomena), and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 82 publications
5
62
1
Order By: Relevance
“…As Kintisch (2015) points out, faster ice cover disappearance leads the lakes that normally freeze in winter to about twice as fast heating as the lakes that are not affected by such process. Ptak et al (2018) emphasize the role of ice season shortening on an increase in temperature of lakes in Poland. An earlier decline of ice cover has an impact on faster formation of thermal stratification, and thus for a longer period only a part of water, including epilimnion, is heated.…”
Section: Resultsmentioning
confidence: 95%
“…As Kintisch (2015) points out, faster ice cover disappearance leads the lakes that normally freeze in winter to about twice as fast heating as the lakes that are not affected by such process. Ptak et al (2018) emphasize the role of ice season shortening on an increase in temperature of lakes in Poland. An earlier decline of ice cover has an impact on faster formation of thermal stratification, and thus for a longer period only a part of water, including epilimnion, is heated.…”
Section: Resultsmentioning
confidence: 95%
“…In the context of global warming, the current patterns of parameters of the ice regime are subject to evident transformations, and numerous studies in the scope suggest a general reduction of the ice season duration (Cai et al 2017;Magee and Wu 2017;Nowak et al 2018). Due to the shift of ice end, the term of development of thermal-density water stratification occurs earlier, and as a consequence the epilimnion layer heats up faster and longer (Ptak et al 2018a). In a broader spatial approach, faster ice end on lakes (temperate and polar zone) contributes to their faster heating in comparison with lakes in which the freezing process does not normally occur (Kintisch 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly important in the daily cycle, as reflected in the dynamic increase in water temperature resulting from solar radiation. Lakes with lower water transparency absorb solar radiation in the shallower water layer, translating into its faster heating (Ptak et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Research concerning pCO 2 and CO 2 by Yang et al (2019) showed that water temperature is one of the primary factors affecting their daily dynamics. Therefore, they are issues important for the functioning of lake ecosystems, particularly in the context of transformations of the thermal regime of lakes , Ptak et al 2018b under the conditions of climate changes. In this context, it is necessary to have detailed knowledge on all components affecting the lake ecosystem -their dynamics and scale of changes in different time scales.…”
Section: Discussionmentioning
confidence: 99%